Burning to read : English fundamentalism and its Reformation opponents - Simpson, James, 1954- (Belknap Press of Harvard University Press, 2007)
Amid present-day conflagrations, this illuminating book reminds us of the sources, and profound consequences, of Christian fundamentalism in the sixteenth century. Simpson focuses on the cultural transformation in early modern England that allowed common people to read the Bible for the first time. The last wave of fundamentalist reading in the West provoked 150 years of violent upheaval; as we approach a second wave, this powerful book alerts us to our peril.